1991
DOI: 10.1007/bf02689924
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Race and Poverty in the Demand for Private Education: The Case of Mississippi

Abstract: Most studies of the demand for private education have treated “white flight” as a response to the proportion of the population that is black in a particular area. The present article, by contrast, considers the possibility that this flight may be from poverty rather than race. The article develops an aggregate demand function for private education from which individual behavior may be inferred, and then applies the model to data from Mississippi. The results suggest that prejudice is directed against poor blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…This finding points to resource reallocation within schools and universities as a potential consequence of immigration. We also acknowledged that a second possibility that some readers will find more realistic is what Conlon and Kimenyi (1991) in their analysis of whites' school choice as a function of race labeled 'irrational prejudice'. The finding that the overall immigrant share affects private school choice at the secondary level, where greater socioeconomic mixing occurs, but not at the primary level, is consistent with the idea of flight related to prejudice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding points to resource reallocation within schools and universities as a potential consequence of immigration. We also acknowledged that a second possibility that some readers will find more realistic is what Conlon and Kimenyi (1991) in their analysis of whites' school choice as a function of race labeled 'irrational prejudice'. The finding that the overall immigrant share affects private school choice at the secondary level, where greater socioeconomic mixing occurs, but not at the primary level, is consistent with the idea of flight related to prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies examine whether the choice between private and public school is influenced by the racial composition of the local population (see, for example, Conlon and Kimenyi, 1991;Fairlie and Resch, 2001;Figlio and Stone, 1997;Lankford and Wyckoff, 1997). These studies generally find evidence of 'white flight' from public schools into private schools when the public schools have large concentrations of blacks or minorities.…”
Section: Introductionmentioning
confidence: 99%
“…We thank these authors for providing their codes. 5 Using the 1980 Census, in which there were separate categories, we find that 85.1% of children enrolled in private schools are enrolled in religious schools.…”
Section: Datamentioning
confidence: 99%
“…Using the U.S. metropolitan areas for 1980 and 1990, they estimate that for every four immigrants who arrive in public high schools, there is one 7 local student who switches to a private school. Some authors have suggested that such a result may be related to racial prejudice among the locals (Conlon and Kimenyi 1991), and others suggest that the cause is lower expected attainment in public school because of "peer-group" effects (Henderson, Mieszkowski, and Sauvageau 1978), or bad signaling of academic quality. Our model is able to provide a theoretical basis for Betts and Fairlie (2003)'s conjecture that, by increasing the pressure on resources in public schools, the arrival of immigrants induces more local parents to opt out of the public system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…41 Table 3 shows the average public share of school funding for each type of student by country, grouped by regime. 42 Figure 5 plots all 35 countries according to the average share of public funding their schools receive, and the variations of the share between different types of students within each country. It is observed that there are three main clusters of countries.…”
mentioning
confidence: 99%